A Study of Dielectric Effects on Resonance Frequency of a Split Ring Shaped Inclusion - Audu, Eliazar Elisha; Eteng, Akaa; Uchendu, Iyemeh Egwenike (European Journal of Applied Sciences, 2023)
Resonator designs are central to the development of subwavelength unit structures of metasurfaces to create exotic and unique electromagnetic properties by modifying the host structure to tune impinging electromagnetic waves. The act of intentional control of propagating electromagnetic fields are actively being explored in wireless radio environment control for sixth generation (6G) and beyond. In this paper, we study the effect of dielectric properties on electric field distribution and resonance frequency of a circular split ring resonator (SRR). The subwavelength resonator structure is modelled and simulated using High Frequency Structure Simulation (HFSS) software. Rogers RO3003 and RO3210 were used at different thickness to study the field distribution and its effect on resonance frequency of the SSR. The results show a decrease in resonance frequency of 38.41% from RO3002 (lower relative permeability of 3) to RO3210 (higher relative permeability of 10.2). With change in Rogers RO3210 thickness from 1mm to 1.525mm, the resonance frequency has changed from 5.5GHz to 5.2313 GHz. This indicates that the material composition of the substrate and the physical dimension of the SRR unit cell affects the resonance frequency of the structure.